CONFLICT RESOLUTION COUNSELING FOR A PEACEFUL FAMILY - Muhamad Subkhan; Bunyamin Maftuf; Elly Malihah; Sri Rumiati; Pat Kurniati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Humans are identical with a difference, because Allah Azza Wajalla created humans in different conditions. In fact, this difference has become a decree of Allah (Sunnatullah). On the other hand, humans are also given the nature of having a feeling of attraction to other types, especially when they hit puberty or adolescence. The feeling of attraction is the beginning of the feeling of belonging or the feeling of love. So for those who have reached a mature or mature age, they will focus their love on the desire to build a family or a household. Conflict in a household is a reality that cannot be avoided. Conflict can have a positive or negative impact. So managing conflict requires maturity to think. However, not all families are able to resolve their conflicts, therefore counseling is needed in resolving a conflict in the family, so that a peaceful family can be created or we are left with a sakinah mawadah warohmah family.